AN ANALYSIS OF OEDIPUS COMPLEX OF MICHAEL BERG IN THE READER MOVIE - Suswanto Ismadi Megah (CAHAYA PENDIDIKAN, 2018)
A This study analyzed of psycho-analysis, particularly the Oedipus complex problem faced by  the main character named  Michael Berg in the film The Reader based on  The characteristics of Oedipus Complex theory. This study employed a descriptive qualitative .The data obtained from the transcript of subtitle of the movie “ The Reader “ movie  as primary data. In addition,  secondary data was  from paper, books, article. The data collection in this study was completely done through  watching, giving marks and categorizing the data before do the analysis from the dialogue, situation who delivered in the movie which becomes the main data in this study. The result of the analysis this study show that the main character in “ The Reader” movie has the Oedipus complex’s characteristics. Based on the analysis in this study why main character loved older woman duet his closed relationship his mother which cuased gap with his father. Te old woman was a reflection of his mother.